Antecedents of willingness to provide pharmaceutical services for mental illness individuals - Nesya Jeihan Daniswara; Setiyo Budi Santoso; Prasojo Pribadi (Intelektual Pustaka Media Utama, 2022)
Pharmacists play a role in providing health care for mental illness patients such as medication management, providing drug information, medication counseling, and facilitating treatment adherence strategies. This study aimed to determine the effect of stigma, attitude and belief on the willingness to provide pharmaceutival services for mental illness individuals. This study design is a quantitative correlational study with a cross sectional approach. The sampling technique in this study used a purposive sampling approach. The sample used was 376 respondents with the inclusion criteria of undergraduate and diploma pharmacy students in Central Java, Indonesia. Data analysis were conducted in structural equation modeling - partial least square (SEM-PLS). The statistical results showed that attitudes had a positive effect on the willingness of pharmacy students to provide pharmaceutical services for mental illness individuals (p<0.05). However, stigma and belief do not affect the willingness of pharmacy students to provide pharmaceutical services for mental illness individuals (p>0.05). This study suggested conducting learning evaluations such as improving mental health literacy and interdisciplinary collaboration.